Association of Phomopsis vexans with Eggplant (Solanum melongena) Seeds, Seedlings and its Management - Islam, MR; Meah, MB (The Agriculturists, 2012)
Incidence of Phomopsis vexans on farmers’ eggplant seeds collected from different areas of Bangladesh varied from 0.0 to 7.5%. The highest incidence of P. vexans (7.50 %) was recorded in cultivar Dohazari and Rupgonj L collected from Chandanish and Rupgonj, respectively. No incidence of P. vexans was observed in the cultivar Katabegun and Jessore-L collected from Pabna and Monirampur, respectively. Very low seed infection was recorded in the cultivar Shingnath, Bijoy, Ishurdi-Land Longla-long collected respectively from Chandina, Modhukhali, Ishurdi and Kulaura. Seeds collected from HRC of BARI had higher seed infection by P. vexans. Seed selection had a significant impact on the incidence of P. vexans. Use of apparently healthy seed was found effective in controlling damping off, tipover and seedling blight of eggplant. The least incidence of P. vexans (1.25%) and the highest germination (86.75%) were recorded in apparently healthy seed as against 6.5% seed infection and 60% seed germination recorded in farmer’s seed. In the net house, the least incidence of damping off, tipover and seedling blight were recorded in case of apparently healthy seed. Seed treatment with hot water (56 °C for 15 minutes), garlic (Allium cepa L) bulb extract and Allamanda (Allamanda cathertica L) leaf extract, Trichoderma harzianum CP, Trichoderma harzianum T22 and Bavistin were found promising in controlling seedling diseases in the nursery and in increasing the seed germination. Combinations of apparently healthy seed (T2), treated with garlic bulb extract (T3) and soil treated with T. harzianum CP (T11) completely controlled damping off, tipover and seedling blight in the nursery bed and increased seed germination by 48.83% over control. Keywords: Eggplant; incidence; seed; seedling; disease; Phomopsis vexans; management DOI: http://dx.doi.org/10.3329/agric.v9i1-2.9474 The Agriculturists 2011; 9(1&2): 8-17